Moss and lichen asexual propagule dispersal may help to maintain the extant community in boreal forests. Issue 9 (16th September 2019) - Pasiche‐Lisboa, Carlos J.; Booth, Tom; Belland, René J.; Piercey‐Normore, Michele D.
Abstract: Asexual propagules produced by mosses and lichens may help to maintain their community composition in boreal forests. Understanding the factors affecting the deposition of asexual propagules and their link with the community composition may reveal how the community is maintained. The goal of this study was to understand how weather, the community of lichens and mosses, the dominant tree species in a stand, substrata, and tree aspect influenced and were linked to the deposition of asexual propagules (quantity, size, and type) in boreal forests. Species richness and cover were assessed for the substrata within the tree stands. Traps attached to trees and the ground (substrata) in balsam fir‐, white spruce‐, and poplar‐dominated stands were used to capture asexual propagules. Species and quantity of trapped asexual propagules were linked to the species richness and cover of the extant community. Propagules captured were dominated by lichen thallus fragments and were smaller and in higher quantities during colder times of the year, and in higher quantities and smaller sizes mostly on trees of conifer stands. Moss propagules were captured in low quantities compared to lichen propagules, on the forest floor, but mostly during warmer times of the year. The dispersal of mosses and lichen asexual propagules helps to maintain and is linked to their community in boreal forests. The linkage between asexual propagule deposition and the community (richness and abundance) was observed among lichen and moss communities on poplar trees, conifer trees, or the forest floor of boreal forest stands.